A simple path - Teresa, Mother, Saint, 1910-1997.; Vardey, Lucinda (New York : Ballantine Books, 1995)
The Nobel Peace Prize winner discusses how her personal credo of "love in action" has shaped her life and shows readers how to build a similarly strong and charitable foundation for their lives. Known around the globe for her indefatigable work on behalf of the poor, the sick, and the dying, Mother Teresa has devoted her life to giving hope to the hopeless in more than one hundred and twenty countries. She inspires us all to find a way to translate our spiritual beliefs into action in the world. How has one woman accomplished so much? And what are the guiding principles that have enabled this humble nun to so profoundly affect the lives of millions? Now, in her own words, Mother Teresa shares the thoughts and experiences that have led her to do her extraordinary charitable work, a candid look at her everyday life at the very simplicity and self-sacrifice that give her the strength to move mountains. A simple path gives voice to the remarkable spirit who has dedicated her life to the poorest among us. Just as important as her beliefs are how they are put into action in the world. A simple path also tells the story of the founding of the Missionaries of Charity, their purpose and practice, and the results of their tireless work. Through faith, surrender, and prayer, the missionaries live to serve others; they have improved the lives of countless souls and given dignity to the dying. Their mission has also produced a ripple effect, spreading human compassion to communities where there is need. Through these examples, as well as the uplifting words and guiding prayers of Mother Teresa and those who work with her, everyone can learn how to walk the simple path that Mother Teresa has laid out for us, to help create a truly kinder world for the future. A simple path is a unique spiritual guide for Catholics and non-Catholics alike: full of wisdom and hope from the one person who has given us the greatest model of love in action in our time.
The simple path -- Prayer -- Faith -- Love -- Service -- Peace.
Keywords: Teresa, -- Mother, Saint, -- 1910-1997.; Missionaries of Charity -- Biography; Nuns -- India -- Kolkata -- Biography; Teresa, Mother -- 1910-; Nuns -- India -- Calcutta -- Biography; Missionaries of Charity -- Biography; Teresa, Mother, -- 1910-; Nuns -- India -- Calcutta -- Biography; Missionaries of Charity -- Biography